Leather & lark - Weaver, Brynne (Weaver, Brynne. Ruinous love trilogy, 2024)
"Contract killer Lachlan Kane wants a quiet life working in his leather studio and forgetting all about his traumatic past. But when he botches a job for his boss's biggest client, Lachlan knows he'll never claw his way out of the underworld. At least, not until songbird Lark Montague offers him a deal: use his skills to hunt down a killer and she'll find a way to secure his freedom. The catch? He has to marry her first. And they can't stand each other."--